Effectiveness of Transactional Analysis on Job Fatigue and Job Attachment of Teachers Working in Education - Binyaz, Mojtaba; Azizzadeh, Ruholah; Arefzadeh, Firoz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Teaching can be very stressful, and teachers suffer more mental health problems than other workers. Job burnout occurs due to severe, continuous, and uncontrolled stress and when the work environment demands exceed the individual’s abilities to adapt or succeed. Therefore, this research aimed to determine the effectiveness of transactional analysis on job fatigue and job attachment of teachers working in education. Method: This research method was quasi-experimental and in the form of a pre-test-post-test design with an experimental group and a control group. The statistical population of the current study included all teachers (teachers and principals) of Boyer Ahmad city, from among whom 30 people were selected randomly as a sample. They were randomly divided into two groups: experimental (15 people) and control (15 people). The experimental group was trained with a transactional analysis approach, and the control group received no intervention. A researcher-made job attachment questionnaire and Vodanovich & Kass (1990) job fatigue inventory were used to collect data. The analysis of variance through SPSS-24 statistical software was used to analyze the research data. Results: The results showed that the teaching approach based on Bern’s transactional analysis was effective on the tendency of job fatigue and teachers’ attachment (P<0.01). Conclusion: Considering that the present study has confirmed the positive effect of Bern’s transactional analysis therapy on job fatigue and increasing personal growth, it is suggested to provide the possibility of using TA approach in career counseling centers.